Death by Irish whiskey - Murphy, C. E. (Catie E.) (Murphy, C. E. (Catie E.). Dublin driver mystery., 2024)
When rivalries and revelries during the competition for the best whiskey in Ireland lead to a double murder, Dublin limo driver Megan Malone, with her relationship on the rocks, takes a shot at solving the case.